Climate-Resilient Urban Design from a Biomimicry-Arcology Perspective - Yong, Gabriel Yit Viu (International Journal of Environment, Architecture, and Societies, 2022)
Global climate action initiatives have focussed on either climate mitigation or adaptation in the decarbonisation agenda. The impact of urbanisation is generally overlooked. Urban development alters the environment, including climate, in multiple ways. Therefore, climate actions are unlikely to succeed, even if its goals are achieved, largely because the current paradigm promotes expansion at the expense of nature. This paper presents an alternative perspective on urban design with respect to climate resiliency. It draws primarily from the thoughts that underpin Arcology and Biomimicry from a complex, evolving Earth systems paradigm. It argues that urban development must shift from 2-dimensional gigantism to a compact 3-dimensional form. It further posits that the structure should facilitate greater exchanges, drawing together complementary elements in economy, industry and society, and services into the same structure. Hyper-structures, multi-functional infrastructures, and systems, are required to drive the transition towards a more efficient, low-impact urbanisation paradigm that frees the land for nature to recolonize. Biomimicry provides suitable models and guides through species that thrive as well as biomes that have developed in the range of environmental and climatic regions on the planet. A viable approach would be to build on existing transport infrastructure.